1990
DOI: 10.1111/j.1365-2141.1990.tb02660.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of Band 3 variants of human red cell membranes in some different populations

Abstract: A variant of Band 3, the major protein of the erythrocyte membrane, was observed by Mueller and Morrison in 1977 in 6-7% of healthy blood donors on sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) of erythrocyte membranes treated with pronase. Pronase treated red cells containing this first recognized variant [here designated 'Band 3-Memphis (m)'] section had two bands of about 63,000 and 60,000 Mr while pronase treated normal cells had only the lighter Mr band. The present study includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…One of these variants is the Memphis polymorphism (rs5036), which is well documented to be variable among many widespread world populations. [34][35][36][37] Remarkably, the ancestral allele at this locus, as determined by comparison with a number of outgroup species, 34,38,39 is rare (typically less than 0.10) in all populations where the SNP is polymorphic. It is notable that the observed frequency of the ancestral Memphis allele is 0.24 in our Indonesian sample, encompassing five different haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…One of these variants is the Memphis polymorphism (rs5036), which is well documented to be variable among many widespread world populations. [34][35][36][37] Remarkably, the ancestral allele at this locus, as determined by comparison with a number of outgroup species, 34,38,39 is rare (typically less than 0.10) in all populations where the SNP is polymorphic. It is notable that the observed frequency of the ancestral Memphis allele is 0.24 in our Indonesian sample, encompassing five different haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to the high rate of consanguineous marriage and the small number of the examined samples. The value of 0.293 is significantly higher than those of other populations such as Caucasians (0.04), American Indians (0.098), African Americans (0.091), Chinese (0.072), Filipinos (0.1), and Mexicans (0.083) (Ranney et al, 1990). Ideguchi et al (1992) noted that a Japanese population consisted of 613 patients and I23 healthy workers of the Fukuoka University Hospital showed a high frequency (0.156) compared to other populations; however, still the frequency of the inhabitants in this island is almost twice as that of the Japanese examined by Ideguchi et al Since there was no survey focused on a small population of the Japanese, thus far it is difficult to predict how wide the population carrying Band 3-Memphis is distributed in Japan.…”
Section: Resultsmentioning
confidence: 90%
“…Sequence analysis of the amino terminal portion of Band 3-Memphis revealed that the lysine at position 56 was replaced by a glutamic acid, which is thought to lead to abnormal electrophoretic mobility on sodium dodecyl sulfate-polyacrylamide gel (SDS-PAGE) (Yannoukakos et al, 1991). Carriers of Band 3-Memphis are asymptomatic and show no morphologic abnormalities of their erythrocytes (Ranney et al, 1990). Functional analyses of erythrocytes containing Band 3-Memphis in homozygotes demonstrated that the transport rate of phosphoenolpyruvate was slightly decreased (Ideguchi et al, 1992).…”
mentioning
confidence: 99%
See 2 more Smart Citations